Peran Pendidikan dan Pelatihan dalam Peningkatan Kapasitas Aparatur Pemerintahan Desa di Kabupaten Kotabaru - M Najeri Al Syahrin; Ismar Hamid; Rachmat Hidayat; Rahmat Nur; Siti Zulaikha; M Nizar Hidayat; Hery Hermawan; Charennina Marsha Diandra (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
This study aims to analyze the role of education and training in enhancing the capacity of village government officials in Kotabaru Regency. The research employed a descriptive qualitative approach, supported by quantitative data from a survey of 200 village officials. Data were collected through in-depth interviews, observations, documentation, and online questionnaires. The findings indicate that training plays a crucial role in improving the knowledge, skills, and work ethics of village officials, particularly in the areas of development planning and digital administration. The most urgent training needs identified include village potential analysis, the preparation of RPJMDes (Village Medium-Term Development Plans) and RKPDes (Village Government Work Plans), and the utilization of e-Government applications such as Siskeudes and SIPADES. The main obstacles to training implementation are long travel distances, limited funding, and training materials that are not fully relevant to field conditions. The study recommends that local governments design continuous, contextual, and needs-based training programs to promote effective and responsive village governance.